Risk-based HACCP model for spaghetti in a university campus - Roscom, Karen Kristine A. (2002)
Spaghetti is the most implicated food in foodborne disease outbreaks in the Philippines. The main objective of the study was to develop a risk-based HACCP model for spaghetti produced in a university campus. The study involved a survey for the development of database for spaghetti, microbial examination of coliforms, E. coli and S. aureus in spaghetti, ground pork, foodhandler's hands and utensils, documentation of process flow and development of a single-sheet HACCP plan for three types of food service. An average weekly volume of 1,535 kilograms of spaghetti is produced in the test campus and translated to 36,840 consumers per week. Spaghetti produced by a concessionaire-type and street-vended type of food service were subject to temperature abuse while on display. Poor personnel hygiene practices were observed. Spaghetti sample from the concessionaire showed presence of E. coli and significantly high amounts of coliform compared to the fastfood and streetfood samples. Preparation, cooking, hot holding and service were found as critical control points. The greatest risks to E. coli, coliform and S. aureus were associated with the raw material, the spaghetti (indicating contamination after cooking) and the foodhandler's hands, respectively. The risk-based HACCP model identified the following operations: receiving, preparation, cooking, hot holding and service. Consumers are advised to consume the spaghetti while hot. Food service providers are advised to get raw materials from reputable resources. Future studies should be done to implement the single-sheet risk-based HACCP model in the food service, examine microbial hazards at different stages of production and conduct regular water analysis in the test campus.